Effects mediated by the α7 nicotinic acetylcholine receptor on cell proliferation and migration in rat adipose-derived stem cells - Marta Pernarella; Roberta Piovesana; Carlo Matera; Alessandro Faroni; Mario Fiore; Luciana Dini; Adam J. Reid; Clelia Dallanoce; Ada Maria Tata (European Journal of Histochemistry, 2020)
Adipose-derived stem cells (ASCs) are an attractive source for regenerative medicine as they can be easily isolated, rapidly expandable in culture and show excellent in vitro differentiation potential. Acetylcholine (ACh), one of the main neurotransmitters in central and peripheral nervous systems, plays key roles in the control of several physiological processes also in non-neural tissues. As demonstrated in our previous studies, ACh can contribute to the rat ASCs physiology, negatively modulating ASCs proliferation and migration via M2 muscarinic receptor (mAChR) activation. In the present work we show that rat ASCs also express α7 nicotinic receptors (nAChRs). In particular, we have investigated the effects mediated by the selective activation of α7 nAChRs, which causes a reduction of ASC proliferation without affecting cell survival and morphology, and significantly promotes cell migration via upregulation of the CXCR4 expression. Interestingly, the activation of the α7 nAChR also upregulates the expression of M2 mAChR protein, indicating a cooperation between muscarinic and nicotinic receptors in the inhibition of ASC proliferation.